Can Early Management of Hypertension by General Practitioners Improve Outcome? - Deborah L Nadler (Radcliffe Medical Media, 2019)
Hypertension and its cardiovascular sequelae remain one of the major causes of death and disability worldwide, and the prevalence of hypertension in the US and Europe is high. Hypertension is a leading modifiable risk factor for cardiovascular events. Pharmacological approaches and lifestyle modification to treat hypertension early have been consistently shown to improve cardiovascular outcomes in primary and secondary prevention. Recent guidelines recommend initiating treatment at lower blood pressure levels, with normal blood pressure being defined as <120/80 mmHg. Calculating risk using a score such as the Atherosclerotic Cardiovascular Disease Risk Calculator is important to enable the general practitioner to give appropriate, individualized care.